Deep margin elevation with one‐year follow‐up: A case report - Mohammad Aljanakh (Clinical Case Reports)
Key Clinical Message Deep margin elevation (DME) is a conservative treatment of a tooth with extensive subgingival caries. It is an alternative approach to more invasive restorative procedures. The DME enables successful tooth isolation to do root canal treatments and enables performing indirect restorations, improving dental function and patient comfort without complications.